2017
DOI: 10.1002/ijgo.12405
|View full text |Cite
|
Sign up to set email alerts
|

Expectations and needs of Ugandan women for improved quality of childbirth care in health facilities: A qualitative study

Abstract: Objective: To describe the experiences, expectations, and needs of urban Ugandan women in relation to good-quality facility childbirth. Methods:Women who had given birth in the 12 months prior to the study were purposively sampled and interviewed, or included in focus groups. Thematic analysis was used, and the data were interpreted within the context of an existing quality of care framework.Results: Forty-five in-depth interviews and six focus group discussions were conducted. Respect and dignity, timely comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
0
4

Year Published

2017
2017
2017
2017

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 33 publications
(75 citation statements)
references
References 11 publications
1
70
0
4
Order By: Relevance
“…The protocol for the study was agreed before data collection began and country‐specific analyses explain the site‐specific study methodology, strengths, and limitations in more detail.…”
Section: Methodsmentioning
confidence: 99%
“…The protocol for the study was agreed before data collection began and country‐specific analyses explain the site‐specific study methodology, strengths, and limitations in more detail.…”
Section: Methodsmentioning
confidence: 99%
“…While women themselves are the “gold standard” for information on their own needs and preferences, healthcare providers and administrators can provide interesting input to explore convergent and divergent perspectives on women's needs. This paper is part of a series on the BOLD project formative research; other aspects of the project are described in detail elsewhere in this Supplement …”
Section: Introductionmentioning
confidence: 99%
“…While the data are situated in the local health systems, the contextual enablers and barriers are common to many low‐resource maternity care facilities. The richness of data from multiple perspectives provided a comprehensive view on labor monitoring from the key stakeholders, and supplements the findings from other papers in this Supplement . This study may have been limited by the self‐reported practices from the health professionals, which can lead to social desirability bias, resulting in a narrative of “ideal situation” rather than the “actual situation” of labor monitoring.…”
Section: Discussionmentioning
confidence: 81%
“…Only Health Center III and above levels have the capacity to provide maternity services. More details of the study settings can be found in the study protocol and country‐specific analyses in this Supplement . Facilities were chosen based on the following criteria: (1) having at least 1000 births per year; (2) being a major healthcare facility in the region; (3) not being a primary health unit; (4) having relatively stable access to skilled birth attendants, and to the provision of cesarean delivery, augmentation of labor, assisted vaginal birth, and good intrapartum care practices …”
Section: Methodsmentioning
confidence: 99%